Dynamic spillover effects across petroleum spot and futures volatilities, trading volume and open interest - Magkonis, Georgios; Tsouknidis, Dimitris (My University, 2017)
This paper examines the existence of dynamic spillover effects across petroleum based commodities and among spot-futures volatilities, trading volume and open interest. Realized volatilities of spot-futures markets are used as inputs to estimate a VAR model following Diebold and Yilmaz (2014, 2015) and distinguish dynamic spillovers in total and net effects. Results reveal the existence of large and time-varying spillovers among the spot-futures volatilities and across petroleum-based commodities when examined pairwise. In addition, speculative pressures, as reflected by futures trading volume, and hedging pressures, as reflected by open interest, are shown to transmit large and persistent spillovers to the spot and futures volatilities of crude oil and heating oil-gasoline markets, respectively.
Keywords: Dynamic spillovers; Spot and futures markets; Petroleum markets; Trading volume; Open interest